Late Cretaceous paleoenvironments in the Mesopotamian Foreland Basin, northern Arabia: Petrographical, mineralogical, and geochemical evidence from the boundary of the Kometan and Shiranish Formations - Zaman R. Sherwani; Sarmad A. Ali; Ali I. Al-Juboury; Harry Rowe; Giovanni Zanoni; Ahmed M. Abdelhameed; Nagham Omar; Nasir Alarifi (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Paleoenvironmental conditions across the Jurassic–Cretaceous boundary from northern Arabia: Facies analysis, mineralogical and geochemical implications - Alaa M. Al-Wazan; Ali I. Al-Juboury; Nisreen M. Aziz; Ahmed H. Al-Obeidi; Nasir Alarifi; Harry Rowe; Giovanni Zanoni; Justyna Kowal-Kasprzyk; Anna Waśkowska; Nagham Omar; Fathy Abdalla (Journal of African Earth Sciences, 2026)

Corrigendum to “Paleoenvironment, paleoclimate, and stratigraphy controls on the mineralogy of the Devonian-Carboniferous Ora Formation [Iraq J. African Earth Sci. 230 (2025) 105730 1-16] - Mohammed A. Sulaiman; Ali Al-Juboury; Ahmed H. Al-Obeidi; Rebwar H. Rasool; Nasir Alarifi; Giovanni Zannoni; Rowe Harry; Nagham Omar (Journal of African Earth Sciences, 2025)

Corrigendum to “Spatial change in carbonate precipitation and weathering in response to the Palaeocene-Eocene Thermal Maximum warming from northern Iraq” [J. African Earth Sci. 232 (2025) 105824] - Ali Al-Juboury; Noor T. Al-Taee; Ahmed N. Al-Fattah; Mohammed A. Al-Haj; Imad M. Ghafor; Ahmed H. Al-Obeidi; David L. Dettman; Rowe Harry; Giovanni Zannoni; Raafat M. El Attar; Nasir Alarifi (Journal of African Earth Sciences, 2025)

Spatial change in carbonate precipitation and weathering in response to the Paleocene-Eocene Thermal Maximum warming from northern Iraq - Ali Al-Juboury; Noor T. Al-Taee; Ahmed N. Al-Fattah; Mohammed A. Al-Haj; Imad M. Ghafor; Ahmed H. Al-Obeidi; David L. Dettman; Rowe Harry; Giovanni Zannoni; Raafat M. El Attar; Nasir Alarifi (Journal of African Earth Sciences, 2025)

Paleoenvironment, paleoclimate, and stratigraphy controls on the mineralogy of the Devonian-Carboniferous Ora Formation, Iraq - Mohammed A. Sulaiman; Ali Al-Juboury; Ahmed H. Al-Obeidi; Rebwar H. Rasool; Nasir Alarifi; Giovanni Zannoni; Rowe Harry; Nagham Omar (Journal of African Earth Sciences, 2025)

Mineralogy and geochemistry of the middle to upper jurassic sargelu, naokelekan, and barsarin formations from northeastern Iraq: Implications for paleoenvironmental, provenance, and tectonic setting proxies - Rebwar H. Rasool; Sarmad A. Ali; Ali I. Al-Juboury; Nasir Alarifi; Fadhil A. Lawa; Harry Rowe; Giovanni Zanoni; David L. Dettman (Journal of African Earth Sciences, 2025)

Mudstone diagenesis in the Cenomanian–Turonian Eagle Ford Group in the San Marcos Arch area. PART I: Chemostratigraphy, early diagenesis, bitumen expulsion and migration pathways - Lucy T. Ko; Robert G. Loucks; Harry Rowe; Robert M. Reed; J. Evan Sivil; Rieko Adriaens (Marine and Petroleum Geology, 2025)

Corrigendum to ‘Mudstone diagenesis with depth and thermal maturity in the Cenomanian–Turonian Eagle Ford Group. PART II: Diagenetic processes and paragenetic sequence’ [Mar. Petrol. Geol. 170 (2024) 107085 1–39] - Lucy T. Ko; Robert G. Loucks; Harry Rowe; Rieko Adriaens; J. Evan Sivil; Gilles Mertens (Marine and Petroleum Geology, 2024)

Mudstone diagenesis with depth and thermal maturity in the Cenomanian–Turonian Eagle Ford group. PART II: Diagenetic processes and paragenetic sequence - Lucy T. Ko; Robert G. Loucks; Harry Rowe; Rieko Adriaens; J. Evan Sivil; Gilles Mertens (Marine and Petroleum Geology, 2024)

Paleoenvironmental conditions across the Coniacian-Santonian in the Kometan Formation, northeastern Iraq: Insights from planktonic foraminifera distribution, mineralogy and geochemistry - Mohammed A. Sulaiman; Ali I. Al-Juboury; Majid M. Al Mutwali; Irfan Sh Asaad; David L. Dettman; Nasir Alarifi; Fathy Abdalla; Giovanni Zanoni; Harry Rowe (Journal of African Earth Sciences, 2024)

Depositional environments and thermal maturity of the hydrocarbon source rocks in the Devonian–Early carboniferous Ora Formation from palynological organic petrographic investigations in northern and western Iraq - R.S. Al-Auqadi; A.I. Al-Juboury; M.W. Alkhafaji; N. Alarifi; W.A. Makled; Harry Rowe; Giovanni Zanoni; D.L. Dettman (Journal of African Earth Sciences, 2024)

Utility of wastewater genomic surveillance compared to clinical surveillance to track the spread of the SARS-CoV-2 Omicron variant across England - Franziska S. Brunner; Alexander Payne; Edward Cairns; George Airey; Richard Gregory; Natalie D. Pickwell; Myles Wilson; Matthew Carlile; Nadine Holmes; Verity Hill; Harry Child; Jasmine Tomlinson; et al. (Water Research, 2023)

A comparative study of the paleoclimate, paleosalinity and paleoredox conditions of Lower Jurassic-Lower Cretaceous sediments in northeastern Iraq - Nagham Omar; Tom McCann; Ali I. Al-Juboury; Sven Oliver Franz; Giovanni Zanoni; Harry Rowe (Marine and Petroleum Geology, 2023)

High influx of carbon in walls of agglutinated foraminifers during the Permian–Triassic transition in global oceans - Galina P. Nestell; Merlynd K. Nestell; Brooks B. Ellwood; Bruce R. Wardlaw; Asish R. Basu; Nilotpal Ghosh; Luu Thi Phuong Lan; Harry D. Rowe; Andrew Hunt; Jonathan H. Tomkin; Kenneth T. Ratcliffe (International Geology Review, 2015)

Dominance of putative marine benthic Archaea in Qinghai Lake, north‐western China - Hongchen Jiang; Hailiang Dong; Bingsong Yu; Qi Ye; Ji Shen; Harry Rowe; Chuanlun Zhang (Environmental Microbiology, 2008)
Summary Recent studies have revealed important and versatile roles that Archaea play in a wide variety of environmental processes on Earth. In this study, we investigated the abundance and diversity of archaeal communities in lake water and a 5 m sediment core collected from Qinghai Lake on the Tibetan Plateau, north‐western China. An integrated approach was employed including geochemistry, quantitative polymerase chain reaction (Q‐PCR) and 16S rRNA gene analysis. Here, we show that Archaea dominated the prokaryotic community in the lake sediments. Members of putative marine benthic groups [Marine Benthic Group (MBG)‐B, ‐C and ‐D] and Miscellaneous Crenarchaeotic Group (MCG) were dominant, many of which were previously reported to be predominantly present in deep‐sea environments. These results demonstrate that these groups are not limited to marine sediments. Despite their ubiquitous presence in aquatic environments, metabolic functions of these important groups largely remain unknown. Whereas many of these groups (such as MBG‐B and ‐D) have typically been found in methane‐hydrate deposits in marine environments, our carbon isotopic and molecular results from Qinghai Lake sediments indicate a lacustrine origin.